Implementation of the Blended Learning Method to Enhance Clinical Reasoning among Nursing Students - Arisudhana, Gede Arya Bagus; Martini, Ni Made Dwi Ayu (Fakultas Ilmu-ilmu Kesehatan, 2022)
Clinical reasoning has an important role in nursing care. Therefore, an appropriate learning model is needed to produce great clinical reasoning among nursing students. The blended learning method is a flexible and technology-based learning model that has the potential to improve nursing students’ clinical psychomotor skills and overall performance. This study aims to determine the effect of the blended learning method on the clinical reasoning ability of nursing students. This was a quasi-experimental study that used a pretest-posttest design and a control group. The number of samples was 35 respondents in each group. The samples were recruited using a simple random sampling method. The intervention was conducted for 14 weeks in the intervention group. Clinical reasoning was measured using the Clinical Reasoning Assessment Tools (CRAT). Data were then analyzed using the Mann-Whitney test. There were differences in the clinical reasoning ability between the experimental group (p <0.001) and the control group (p = 0.128). A positive effect was found between the blended learning method and clinical reasoning ability among nursing students. Thus, a flexible learning process can provide repetition and continuity of the learning process and improve the students' critical thinking processes.